Observation of Terahertz Vibrations in the Nitrogenase FeMo-cofactor via Femtosecond Pump Probe Spectroscopy - Delfino, Ines (2010)
We have used Impulsive Coherent Vibrational Spectroscopy (ICVS) to study the FeMo-cofactor of nitrogenase from Azotobacter vinelandii as the extracted small molecule ‘FeMoco’. In the ICVS experiment, a 15 fs visible laser pulse pumps the sample to an excited electronic state, and a second <10 fs pulse probes the change in transmission as a function of the time delay. FeMoco was observed to relax to the ground state by a single exponential decay with a time constant of ~200 fs. Superimposed on this relaxation are oscillations caused by the coherent excitation of vibrational modes in both excited and ground electronic states. Fourier transformation reveals the FeMoco vibrational frequencies that are coherently excited by the short laser pulse. The frequencies obtained by the ICVS technique were compared with values from normal mode calculations. The strongest ICVS bands are at 215 and 420 cm(−1). The 420 cm(−1) band is attributed to Fe-S stretching motion, whereas the 215 cm(−1) band, which is the strongest feature in the spectrum, is attributed to a breathing mode of FeMoco. Over the years, nitrogenase and FeMoco have resisted characterization by resonance Raman spectroscopy. The current results demonstrate the promise of ICVS as an alternative probe of FeMoco dynamics.